Stress and Coping Mechanisms Among Families of Critically Ill Patients in the Intensive Care Unit - Sulistiyani, Sulistiyani; Utami, Theresia Febriana Christi Tyas (Fakultas Kesehatan, Universitas Nurul Jadid, 2024)
Introduction: Families of critically ill patients often experience psychological stress due to the uncertainty and emotional burden of intensive care environments. Objectives: This study aimed to examine the relationship between stress levels and coping mechanisms among family members of patients admitted to the Intensive Care Unit (ICU). Methods: A quantitative analytic design with a cross-sectional approach was used, involving 30 respondents selected through quota sampling. Data were collected using structured questionnaires to measure stress levels and coping strategies, and analyzed using Spearman’s rho correlation. Results: The results showed that 60.0% of respondents experienced high levels of stress (Level IV), and 70.0% employed maladaptive coping mechanisms. A moderate positive correlation was found between stress and coping (r = 0.365, p = 0.024), indicating that higher stress levels were associated with an increased use of maladaptive strategies. Conclusions: The study concludes that family members of ICU patients are prone to psychological distress and often lack effective coping mechanisms, highlighting the need for family-centered interventions to support emotional resilience and adaptive coping.